2015
DOI: 10.3923/rjmp.2015.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-inflammatory and Analgesic Activities of Cymbopogon citratus In vivo-Polyphenols Contribution

Abstract: Cymbopogon citratus is one of the most common herbs used in folk medicine due to its anti-inflammatory and antioxidant properties. Taking into account these properties showed on in vitro assays, the aim of this study was to evaluate the anti-inflammatory and analgesic activities of C. citratus leaves infusion (CcE) and its flavonoid-rich (CcF) and tannin-rich (CcT) fractions. The evaluation of the anti-inflammatory activity was performed in the carrageenan-induced rat paw oedema model. Both central and periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 31 publications
(41 reference statements)
0
5
0
Order By: Relevance
“… 26 Furthermore, C citratus was investigated for its analgesic and antipyretic properties, and previous research has suggested that the essential oil from C citratus displayed strong analgesic and antipyretic properties both in central and peripheral analgesic activities. 26 , 27 C hystrix is another ingredient whose chemical composition in essential oil was reported, which dominantly contained citronella (citronellal, citronellol, and geraniol). 28 Citronella, which is commonly used as an effective insect repellent, also exhibited analgesic and anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Furthermore, C citratus was investigated for its analgesic and antipyretic properties, and previous research has suggested that the essential oil from C citratus displayed strong analgesic and antipyretic properties both in central and peripheral analgesic activities. 26 , 27 C hystrix is another ingredient whose chemical composition in essential oil was reported, which dominantly contained citronella (citronellal, citronellol, and geraniol). 28 Citronella, which is commonly used as an effective insect repellent, also exhibited analgesic and anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…Essential oil of C. limon exhibited anti-inflammatory effects by reducing cell migration, cytokine production and protein extravasation induced by carrageena (Amorim et al, 2016). Garcia et al (2015) demonstrated the anti-inflammatory and analgesic properties of C. citratus. Z. officinale essential oil contains fragrant compounds like zingiberene, curcumene, camphene, bisabolene, citral and linalool (Mpondo et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…The inflammatory mediator NO is derived from the amino acid L-arginine by the iNOS enzyme. Drugs that can inhibit NO production can treat acute and chronic inflammatory symptoms (15,16).…”
Section: Discussionmentioning
confidence: 99%